1999
DOI: 10.1038/sj.ejcn.1600866
|View full text |Cite
|
Sign up to set email alerts
|

Low molecular weight plasma antioxidants and lipid peroxidation in maternal and cord blood

Abstract: Objective: To determine the concentrations of the low molecular weight antioxidants urate, bilirubin, albumin and sulphydryl groups and to measure lipid peroxidation levels in pair-matched maternal and cord blood plasma. Design: Venous blood plasma concentrations of urate, bilirubin, albumin and sulphydryls were determined in healthy pregnant women and in pair matched umbilical cords. The ability of maternal and cord plasma to withstand Cu 2 -induced lipid peroxidation was assessed by measuring the production … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
0
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 25 publications
2
16
0
3
Order By: Relevance
“…This conclusion is in agreement with the results of previous studies. The susceptibility of cord plasma to in vitro oxidation by Cu 2ϩ has been recently reported to be lower in comparison with maternal plasma (8). The measured and calculated TRAP values were also higher in newborns than in adults (6) and decreased postnatally with age (7).…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…This conclusion is in agreement with the results of previous studies. The susceptibility of cord plasma to in vitro oxidation by Cu 2ϩ has been recently reported to be lower in comparison with maternal plasma (8). The measured and calculated TRAP values were also higher in newborns than in adults (6) and decreased postnatally with age (7).…”
Section: Discussionmentioning
confidence: 77%
“…Similarly, higher levels of selenium and other important antioxidants such as sulfhydryl groups have also been reported in newborn plasma (8,12). This suggests that the levels of some antioxidants are up-regulated in infants to compensate for increased oxidative stress at birth.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…Терапевтичні ефекти препарату, очевидно, значною мірою визначаються здатністю компонентів, які входять до його складу, стимулювати спо-живання клітинами кисню і глюкози, що має велике значення при багатьох патологічних станах [6][7][8][9]. Також показано, що пуповин-но-плацентарна або кордова кров багатша на біологічно активні фактори порівняно з кров'ю іншого походження [1][2][3][4][5]10]. Була отримана фракція до 5 кДа з кордової крові великої рогатої худоби та продемонстровано її цукрознижувальну і репаративну дію [11,12].…”
Section: вступunclassified
“…The antioxidant efficiency of vitamin E appears to be greatly enhanced by regeneration of the vitamin from its oxidised products (143). Appreciation of other antioxidants (144)(145)(146) has developed the notion that while vitamin E protects lipids other antioxidants must recycle vitamin E. The other major antioxidants are coenzyme Q and vitamin C (147,148) Regeneration of a-tocopherol from its tocoperoxyl radical have been demonstrated by vitamin Another explanation for the low levels of cc-TQ in tissues is that the tocopherol may be one of the last antioxidant substances to be consumed during oxidative stress. Burton and Ingold, found that other antioxidants such as sulphydryl groups in proteins were found to be used preferentially to tocopherols during oxidations initiated by free radicals in human plasma (28,153).…”
Section: ) Vitamin E Is Poor Inhibitor Of Reactions 1 and 2 (123)mentioning
confidence: 99%